2015
DOI: 10.1056/nejmoa1415227
|View full text |Cite
|
Sign up to set email alerts
|

Paternally InheritedIGF2Mutation and Growth Restriction

Abstract: In humans, mutations in IGF1 or IGF1R cause intrauterine and postnatal growth restriction; however, data on mutations in IGF2, encoding insulin-like growth factor (IGF) II, are lacking. We report an IGF2 variant (c.191C→A, p.Ser64Ter) with evidence of pathogenicity in a multigenerational family with four members who have growth restriction. The phenotype affects only family members who have inherited the variant through paternal transmission, a finding that is consistent with the maternal imprinting status of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
150
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(160 citation statements)
references
References 26 publications
7
150
0
3
Order By: Relevance
“…Moreover, this inference is wrong, based on GTEx gene expression data, which, as noted above, indicates that this is at best a very minor IGF2 mRNA species in multiple human tissues. One example of the problems created by this type of incorrect information may be found in the recently published analysis of a family with apparent Silver-Russell syndrome, including both pre-and post-natal growth deficiencies (74). DNA sequencing revealed that the genomes of all affected members harbored a heterozygous nonsense mutation in IGF2 that prevented production of the IGF2 protein, and indeed accumulation of IGF2 in the blood of the subjects was substantially reduced from normal concentrations (74).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this inference is wrong, based on GTEx gene expression data, which, as noted above, indicates that this is at best a very minor IGF2 mRNA species in multiple human tissues. One example of the problems created by this type of incorrect information may be found in the recently published analysis of a family with apparent Silver-Russell syndrome, including both pre-and post-natal growth deficiencies (74). DNA sequencing revealed that the genomes of all affected members harbored a heterozygous nonsense mutation in IGF2 that prevented production of the IGF2 protein, and indeed accumulation of IGF2 in the blood of the subjects was substantially reduced from normal concentrations (74).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Silver-Russell syndrome patients carrying a maternal uniparental disomy of chromosome 7 (UPD7) usually present with low levels of IGF1 (79,81). Very recently, the first family with a paternally inherited IGF2 mutation and growth restriction was reported, indicating that IGF2 not only is a mediator of intrauterine development but also contributes to postnatal growth (82). This confirmed an earlier observation of a patient with a paternally transmitted severe intrauterine growth retardation (IUGR) with a translocation breakpoint disrupting regulation of IGF2 (83).…”
Section: Gh Deficiencymentioning
confidence: 99%
“…Recent studies have identified epimutation (hypomethylation) of the paternally derived H19 ‐differentially methylated region (DMR) at the imprinting control region 1 (ICR1) on chromosome 11p15.5 in ∼45% of SRS patients and maternal uniparental disomy 7 (upd(7)mat) in 5–10% of SRS patients, in addition to rare underlying factors such as duplications of maternally derived chromosome 11p15.5 involving CDKN1C at the ICR2 just proximal to the ICR1, relatively mild gain‐of‐function mutations of CDKN1C , loss‐of‐function mutations of IGF2 , epimutation (hypomethylation) of the IG‐DMR and/or the MEG3 ‐DMR on chromosome 14q32.2 imprinted region of paternal origin, upd(14)mat, upd(16)mat, and upd(20)mat [Eggermann, 2010; Binder et al, 2011; Brioude et al, 2013; Poole et al, 2013; Azzi et al, 2014; Begemann et al, 2015; Kagami et al, 2015; Nakashima et al, 2015]. Here, we report an SRS patient with somatic mosaicism for upd(11)mat that was identified by buccal cell analysis.…”
Section: To the Editormentioning
confidence: 99%